Molecular and imaging biomarkers of local inflammation at 2 years after anterior cruciate ligament injury do not associate with patient reported outcomes at 5 years. Issue 3 (March 2020) - Struglics, A.; Turkiewicz, A.; Larsson, S.; Lohmander, L.S.; Roemer, F.W.; Frobell, R.; Englund, M.
Summary: Objective: To estimate the association between molecular or imaging inflammatory biomarkers at 2 years after anterior cruciate ligament (ACL) injury and patient-reported outcomes at 5 years. Methods: For 116 ACL-injured patients, molecular biomarkers of inflammation (synovial fluid and serum cytokines) and Hoffa- and effusion-synovitis as visualized on magnetic resonance imaging (MRI) were assessed 2 years post-injury. Knee injury and Osteoarthritis Outcome Score (KOOS) and SF-36 were assessed at 2 and 5 years. We used multiple imputation to handle biomarker values that were below the level of detection or missing, and linear regression for statistical analyses. Results: None of the synovial fluid cytokines or imaging biomarkers of inflammation at 2 years were associated with any of the patient-reported outcomes at 5 years. With each log10 unit higher of serum tumor necrosis factor concentration the knee-related quality of life of KOOS was increased (i.e., better outcome) by 35 (95% confidence interval 7 to 63) points. No other serum biomarker measured at 2 years was associated with patient-reported outcome at 5 years. Conclusion: Local joint inflammation assessed by biomarkers in synovial fluid and Hoffa- and effusion-synovitis on MRI at 2 years after an ACL injury did not associate with patient-reported outcomes at 5 years. Thus, chronic inflammation in the ACL-injured knee, as reflected by the biomarkers studied here, seems not to be a key determinant for the long-term patient-reported outcomes.